Effect of seedling age on growth and yield of two rice (Oryza sativa L.) varieties transplanted in Saline Coastal Area of Baros, Yogyakarta - Riza Afrinda; Budiastuti Kurniasih (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
Marginal land along the coast should be utilized to increase the national rice production. In addition, the use of saline resistant varieties, it is necessary to determine the best seedling age for saline soil. This study aimed to evaluate the growth and yield responses of two rice varieties transplanted at different seedling age on saline soil. The experiment was arranged in a factorial Randomized Completely Block Design (RCBD) with three replications, conducted at saline coastal area of Baros, Yogyakarta, starting from January to June 2017. The first factor was rice varieties, consisting of Dendang and IR-64. Meanwhile, the second factor was the seedling age, consisting of 2 and 4 weeks after sowing (WAS) seedlings. The results showed that the growth and yield of two rice varieties (Dendang and IR-64) showed significant difference, and Dendang showed a better performance than IR-64. The higher yield of Dendang compared to IR-64 was supported by higher plant growth (shoot dry weight) and yield components (number of seeds per panicle, seed weight per plot, and productivity). The 2 and 4 WAS seedlings did not give significantly different effects on nearly all growth variables. However, 2 WAS Dendang rice seedlings had higher shoot dry weight. Meanwhile, IR-64 had higher leaf greenness in 4 WAS seedlings compared to that in 2 WAS seedlings.